CRITICAL ANALYSIS OF PATHYA W.S.R YAVAGU KALPANA - Jai Kumar Singh*; Pooja Nanda; Satya Manav Dayal (AYUSHDHARA, 2019)
To maintain the health of a healthy person Acharyas had described various do’s and don’ts, much as Ritu Charya (seasonal regime), Dinacharya (Diurnal regime) etc. The concept of Pathya (whole some) and Apathya is one such concept. Acharyas had also extended this concept as a part of treatment of disease. So it is not only beneficial to maintain the health but also to cure the disease. Yavagu is a good Pathya Kalpana in Ayurveda. Rice, the main ingredient in Yavagu is rich in carbohydrate and its easily digestive property with high nutritive value; make it the appropriate food article for patients as well as healthy persons, who have Mandagni (low digestive capacity). It also works as the media for various drugs by utilizing drug decoctions in place of water and drug power as adjuvant. Standardization of Yavagu under Pathya Kalpana is found to be necessary in this era to promote its usage, prescription, efficacy and availability.